Analisis Dampak Penerapan Hazard Analysis And Critical Control Point (HACCP) Terhadap Jaminan Mutu Dan Keamanan Produk Perikanan (Telaah Pustaka) - Yuliana Farahita; Junianto (Jurnal Serambi Engineering, 2024)
Fish products are rich in protein, but are very susceptible to spoilage. Every fish processing industry is required to implement the Hazard Analysis and Critical Control Point (HACCP) system to improve quality assurance and safety. The aim of this research is to investigate how the implementation of HACCP system affects the quality assurance and safety of fishery products in the fish processing industry. Various research literature from national and international journals is used as an exploratory descriptive method. The results of the research indicate that the implementation of HACCP can have a positive impact on quality assurance, such as improved product quality, better standardisation of processes, increased production efficiency, reduced microbiological contamination, fewer product recalls, as well as improved market competitiveness and increased consumer confidence.